2012
DOI: 10.1111/j.1365-2036.2011.04983.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and patient outcomes with lubiprostone for up to 52 weeks in patients with irritable bowel syndrome with constipation

Abstract: SUMMARY BackgroundIrritable bowel syndrome with constipation (IBS-C) significantly decreases quality of life and the ability to perform daily living activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 19 publications
4
48
0
1
Order By: Relevance
“…In the most common -chronic constipation, laxatives remain the mainstay of pharmacological intervention, although new drugs have recently been introduced. These include prucalopride, a selective 5-HT4 receptor agonist, which facilitates enteric cholinergic and nitrergic activities to promote intestinal motility (Cellek et al, 2006), and lubiprostone and linaclotide, which, respectively, activate chloride type-2 channels and guanylate cyclase type-C receptors to promote defecation primarily by increasing fluid secretion into the lumen (Lembo et al, 2011;Chey et al, 2012). Such breakthroughs have renewed interest in how best to treat other conditions associated with hypomotility and also with acute or chronic small and/or large intestinal dilation.…”
Section: Introductionmentioning
confidence: 99%
“…In the most common -chronic constipation, laxatives remain the mainstay of pharmacological intervention, although new drugs have recently been introduced. These include prucalopride, a selective 5-HT4 receptor agonist, which facilitates enteric cholinergic and nitrergic activities to promote intestinal motility (Cellek et al, 2006), and lubiprostone and linaclotide, which, respectively, activate chloride type-2 channels and guanylate cyclase type-C receptors to promote defecation primarily by increasing fluid secretion into the lumen (Lembo et al, 2011;Chey et al, 2012). Such breakthroughs have renewed interest in how best to treat other conditions associated with hypomotility and also with acute or chronic small and/or large intestinal dilation.…”
Section: Introductionmentioning
confidence: 99%
“…It is also efficacious in IBS (NNT of 12.5) [56]. Diarrhoea is a side effect, and in practice nausea can be an issue in up to one in five patients, although the mechanism of nausea is unknown [124]. Normally one of these options may be considered if firstline dietary and laxative therapy has failed in patients with IBS and constipation.…”
Section: Targeting Symptoms In Ibsmentioning
confidence: 99%
“…The combined results of 2 large phase III trials (n = 1,171) demonstrated a modest efficacy for overall response (17.9 vs. 10.1%, p = 0.001) [38]. The most common adverse event was nausea (10-25%), which was usually self-limited but caused some discontinuations [39]. …”
Section: Treatments Targeting Constipation In Ibsmentioning
confidence: 99%